The teenage pregnancy on obstetric fistula among women in fistula center at Malalai Hospital, Kabul Afghanistan: A cross-sectional study - Sahak, Mahbooba; Saiqal, Oniba; Salih, Mohibullah (Technium Social Sciences Journal, 2021)
Introduction: Obstetric Fistula is defined as direct communication between the vagina and the bladder (vesicovaginal fistula) and/or between the vagina and the rectum (recto-vaginal fistula). Each year 50.000 to 100.000 new cases of obstetric fistula are globally reported. According to World Health Organization, more than 200 million young women live with unrepair obstetric fistula mostly in sub-Saharan Africa and southeast Asia including Afghanistan. Women with obstetric fistula suffer from frequent urinary or fecal incontinence which causes shame, social segregation, and other health problems. Obstructed labor (due to early marriage and inadequately developed pelvic) constitutes the most common cause of obstetric fistula. Therefore, the current study strived to assess teenage pregnancy on obstetric fistula among women in the fistula center of Malalai Maternity Hospital in Kabul, Afghanistan. Methods: A descriptive cross-sectional study was conducted over a period of one year (2019-2020) with 30 cases of obstetric fistula among women attended at Fistula Center of Malalai Maternity Hospital. Result: Among 30 women current aged with obstetric fistula 66.6 % were between20-37years, the mean age was 33.9±10.2 and the median was 30 years, the max and min range was between 20-56y. 66.6 % cases their marriage-age was between 16-20 y, while marriage age(mean) was 18.4±3.2, most women (60%) their ages in first delivery were between 15-19 y old, the height of the 40% women was less than 150 cm, and 46.7% women had 1-4 parity with mean of 5.2±3.1 and extreme (1-14), duration of labor in 90% were more than one day, majority of cases (60%) was Recto vaginal, 33% vesicovaginal and 7% with a compound type of fistula, 80% of cases were from remote and rural areas. Conclusions The teenage pregnancy and early marriage between (16-20 y old) was the vast majority of obstetric fistula formation, rectovaginal fistula, living in a remote area, short stature less than 150cm, and duration of more than one day have been seen. teenage pregnancy and obstetric fistula are preventable conditions. These findings suggest that efforts to reduce obstetrical fistula should target teenagers